Notch fatigue behaviour of low-temperature gaseous carburised 316L austenitic stainless steel. Issue 10 (2nd July 2020) - Peng, Yawei; Zhang, Song; Liu, Zhe; Gong, Jianming
ABSTRACT: The influence of low-temperature gaseous carburisation on notch fatigue behaviour of 316L steel under cyclic axial loading was investigated. After carburisation, the carburised case was well distributed at the surface region and was not influenced by the notch geometry. Low-temperature carburisation considerably enhanced the notch fatigue performance, which led to 32% and 44% increase in the endurance limits for the specimens with stress concentration factors K t  = 1.91 and 3.91, respectively. The notch sensitivity of 316L steel reduced after carburisation. Irrespective of the applied stress amplitude, the fatigue crack nucleation sites were always at the notch root surface for the untreated specimens. For the carburised specimens, fatigue cracks nucleation changed from surface at high-level stress to subsurface at low-level stress.